Sosiologi Kesehatan Terhadap Mahasiswa Fakultas Kedokteran Militer Universitas Pertahanan Republik Indonesia - Pannyiwi, Rahmat; Rachman, Arif; Wibowo, Markus (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
The sociology of health is the study of the interaction between social, cultural, and institutional factors on the health of individuals and groups. Students of the Faculty of Military Medicine at the Indonesian Defense University (Unhan RI) are in a unique position because, in addition to pursuing medical education, they are also bound by military values ​​that emphasize discipline, leadership, and physical endurance. This study aims to analyze how the sociology of health perspective plays a role in shaping the behavior, knowledge, and healthy lifestyles of military medical students. The research method used a qualitative descriptive approach with in-depth interviews and questionnaires. The results indicate that social environmental factors, military discipline, and the influence of military health culture have a significant impact on students' mindsets and behaviors in maintaining physical and mental health.